Moral Disagreement and Moral Semantics. (19th June 2016) - Khoo, Justin; Knobe, Joshua
Abstract: When speakers utter conflicting moral sentences ("X is wrong"/"X is not wrong"), it seems clear that they disagree. It has often been suggested that the fact that the speakers disagree gives us evidence for a claim about the semantics of the sentences they are uttering. Specifically, it has been suggested that the existence of the disagreement gives us reason to infer that there must be an incompatibility between the contents of these sentences (i.e., that it has to be the case that at least one of them is incorrect). This inference then plays a key role in a now‐standard argument against certain theories in moral semantics. In this paper, we introduce new evidence that bears on this debate. We show that there are moral conflict cases in which people are inclined to say both (a) that the two speakers disagree and (b) that it is not the case at least one of them must be saying something incorrect. We then explore how we might understand such disagreements. As a proof of concept, we sketch an account of the concept of disagreement and an independently motivated theory of moral semantics which, together, explain the possibility of such cases.